Use of self-oscillations in guidance and control of marine vessels = Primjena vlastitih oscilacija u vođenju i upravljanju plovilima : : doctoral thesis = doktorska disertacija - Mišković, Nikola (N. Mišković ; Fakultet elektrotehnike i računarstva, 2010)
ABSTRACT : This dissertation presents an identification method based on self–oscillations (IS–O) used for the purpose of guidance and control of marine vessels (underwater and surface). The proposed method is described for a general class of nonlinear systems and a general, matrix based algorithm is given for static (Type 0) linear time invariant systems with its modification for discrete–time systems, astatic systems (Type k) and systems with delays. Special attention is devoted to a class of affine nonlinear system models which are used to describe the dynamics of marine vehicle. The main advantage of the proposed method is its applicability during in the field operation and time parsimony. The IS–O method is experimentally tested on two unmanned underwater vehicles and an unmanned surface marine vessel, and comparison to conventional identification methods is given, proving the accuracy of the proposed method on real marine vehicles operating in the field conditions. The identification results are used for the design of heading controllers, distance keeping controllers and line following controllers. Experimental results obtained from real marine vehicles are presented in the thesis. -